Study of Waste Heat Driven Adsorption Cooling System Employing Doped MiL-101(Cr) and Water as Adsorbent Adsorbate Pair - Chakraborty, Anutosh (2016)
This article presents the dynamic behaviors of two bed adsorption chiller utilizing the composite adsorbent “immobilization of NH2, -NO2, -OH groups to MiL-101(Cr)” as adsorbent and water as adsorbate, which is based on the experimentally confirmed adsorption isotherms and kinetics data. The experimentally measured MOFs + water based isotherms and kinetics data are fitted with adsorption isotherm models and linear driving force kinetics equations. Compared with the experimental data of conventional adsorption chiller based on zeolites/silica gel-water system, we found that the newly working pair provides better cooling capacity and performances in terms of COP and adsorption bed size. From numerical simulation, it is also found that the cooling capacity can be increased up to 20 percent of the parent silica gel-water adsorption chiller and the COP can be improved up to 25% more at optimum conditions.